Discrete reconfigurable back-stepping attitude control of reentry hypersonic flight vehicle. (April 2017) - Ren, Zijun; Fu, Wenxing; Yan, Jie; Xu, Bin
A discrete reconfigurable back-stepping controller is proposed to resolve the attitude command tracking problem of hypersonic flight vehicle in reentry mode. The hypersonic flight vehicle dynamic equations are transformed into discrete form based on Euler numerical integration method. Discrete control command is designed via discrete back-stepping. Control allocation strategy is introduced to deal with the resource distributing problem of reaction control system and aero-surfaces. In computer simulation environment, the vehicle tracks command signals precisely and quickly.